2019
DOI: 10.1007/s11695-019-03998-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum Irisin, Adropin, and Preptin in Obese Patients 6 Months After Bariatric Surgery

Abstract: Background/Objectives The reduction of body mass after bariatric surgery affects energy metabolism and may involve changes in irisin, preptin, and adropin production. Subjects and Methods Fifty-five morbidly obese patients with a mean body mass index (BMI) of 45.7 ± 5.8 kg/m 2 were treated with either laparoscopic sleeve gastrectomy(n = 30) or laparoscopic adjustable gastric banding (n = 25). Forty-six (83.6%) were followed-up 6 months after surgery. The control group included 15 healthy non-obese participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 22 publications
0
13
1
Order By: Relevance
“…In previous studies, an association between serum preptin and BMI has been reported [19,23,24]. Nevertheless, we did not determine a correlation between preptin and BMI.…”
Section: Discussioncontrasting
confidence: 54%
“…In previous studies, an association between serum preptin and BMI has been reported [19,23,24]. Nevertheless, we did not determine a correlation between preptin and BMI.…”
Section: Discussioncontrasting
confidence: 54%
“…The effect of weight loss on plasma adropin concentrations was dependent on baseline adropin levels, with a negative correlation between baseline and a decline in concentrations after weight loss 26 . Following bariatric surgery, serum adropin levels increased as part of the change in energy production 27 . Increased serum adropin levels in patients with cardiac cachexia correlated positively with brain natriuretic peptide (BNP) levels and New York Heart Association (NYHA) class and negatively with BMI and serum albumin levels 28 …”
Section: The Role Of Adropin In Regulation Of Metabolic Pathways and mentioning
confidence: 99%
“…26 Following bariatric surgery, serum adropin levels increased as part of the change in energy production. 27 Increased serum adropin levels in patients with cardiac cachexia correlated positively with brain natriuretic peptide (BNP) levels and New York Heart Association (NYHA) class and negatively with BMI and serum albumin levels. 28 Overall, these data support a regulatory role for adropin in the metabolic pathways of glucose and fatty acids and their complications.…”
Section: The Role Of Adropin In Regulation Of Metabolic Pathways Anmentioning
confidence: 99%
“…On the other hand, it has been seen that in mice, the overexpression of adropin reduces weight gain, attenuates hepatosteatosis, increases fatty acid oxidation throughout the body, improves insulin sensitivity, and improves glucose tolerance [ 67 ]. A study of patients who underwent bariatric surgery showed that weight loss increased levels of adropin [ 80 ]. Still, in this respect, there is increasing evidence that adropin is a biomarker of cardiovascular dysfunction, initially because in vitro tests showed that endothelial cells treated with adropin had greater proliferation, migration, formation of a capillary-like tube, and positive regulation of the expression of nitric oxide endothelial synthase (eNOS).…”
Section: Discussionmentioning
confidence: 99%